2015
DOI: 10.1007/s10955-015-1285-y
|View full text |Cite
|
Sign up to set email alerts
|

High-Activity Expansion for the Columnar Phase of the Hard Rectangle Gas

Abstract: We study a system of monodispersed hard rectangles of size m×d, where d ≥ m on a two dimensional square lattice. For large enough aspect ratio, the system is known to undergo three entropy driven phase transitions with increasing activity z: first from disordered to nematic, second from nematic to columnar and third from columnar to sublattice phases. We study the nematic-columnar transition by developing a high-activity expansion in integer powers of z −1/d for the columnar phase in a model where the rectangl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 56 publications
(117 reference statements)
0
26
0
Order By: Relevance
“…The existence of two transitions was rationalized by deriving a high density expansion about the ordered columnar phase. Columnar phases have a sliding instability in which a defect created by removing a single particle from the fully packed configuration splits into fractional defects that slide independently of each other along some direction [15,37,52]. The high density expansion for the 4-NN model showed that the sliding instability is present in only certain preferred sublattices.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of two transitions was rationalized by deriving a high density expansion about the ordered columnar phase. Columnar phases have a sliding instability in which a defect created by removing a single particle from the fully packed configuration splits into fractional defects that slide independently of each other along some direction [15,37,52]. The high density expansion for the 4-NN model showed that the sliding instability is present in only certain preferred sublattices.…”
Section: Introductionmentioning
confidence: 99%
“…An activity z is associated with each rectangle. The system is disordered at low densities and shows columnar order at high densities [48]. We call the phase odd (even) in which the majority of heads (bottom left corner) of the rectangles are in odd (even) rows.…”
mentioning
confidence: 99%
“…Thus, for larger k, the layered-columnar transition would appear to be similar to the disorderedcolumnar transition in k×k hard squares. For this model, high density expansions suggest that the critical density tends to an asymptotic value that is less than one for large k [61]. If this were true, the continuum problem should have two transitions.…”
Section: Discussionmentioning
confidence: 82%